CSR for Employees' and e-WOM Relationship: Case Study in Maritime Business Organization in Turkey - Senbursa, Nihan; Tehci, Ali (Transactions on Maritime Science, 2024)
In the competitive contemporary landscape, Corporate Social Responsibility (CSR) holds paramount importance for enterprises, fostering ethical management and nuanced business understanding while supporting strategic marketing. The transformative impact of information technologies, exacerbated by the COVID-19 pandemic, reshapes corporate communication dynamics. Amidst this, the symbiotic relationship between CSR initiatives and internal communication becomes crucial for organizational success. This research examines the intricate link between CSR and electronic word of mouth communication (e-WOM) intentions among employees. Additionally, it explores whether employment duration significantly influences e-WOM intentions. The research is theoretically based on a model that supports the impact of CSR on behavioral intentions with stakeholder theory and results in e-WOM. The quantitative research method of survey has been implemented. The relationships between the variables were tested using the Correlation and ANOVA analysis. Based on data from 246 employees serving at operations, sales and marketing, sea logistics and business administration departments by convenience sampling method in a Turkish maritime organization serving in container business, the findings reveal a positive correlation between the CSR initiatives and employees’ e-WOM intentions. The study also identifies a discernible impact of employment duration on e-WOM intentions, indicating statistical significance.